Alcaligenes faecalis metallo-β-lactamase in extensively drug-resistant Pseudomonas aeruginosa isolates. (June 2022) - Li, Yue; Zhu, Yiwei; Zhou, Wanqing; Chen, Zhongju; Moran, Robert A.; Ke, Huanhuan; Feng, Yu; van Schaik, Willem; Shen, Han; Ji, Jingshu; Ruan, Zhi; Hua, Xiaoting; et al.
Abstract: Objectives: To characterize Alcaligenes faecalis metallo-β-lactamase (MBL) AFM-2 and AFM-3 from clinical Pseudomonas aeruginosa isolates NDTH10366, NDTH9845 and WTJH17. Methods: Clinical isolates were whole-genome sequenced using the Illumina and Oxford Nanopore platforms. MICs of clinical isolates and transformants containing MBL genes were determined using broth microdilution methods. Kinetic parameters of purified AFM and NDM-1 were measured using a spectrophotometer. The AFM structure was modelled with SWISS-MODEL. Results: NDTH10366 and NDTH9845 were extensively drug-resistant (XDR) isolates carrying bla AFM-2 and multiple copies of bla KPC-2, whereas WTJH17 was an XDR isolate carrying bla AFM-3 . The plasmid-borne bla AFM-2 and bla AFM-3 genes are associated with a novel IS CR element, IS CR29 . AFM-2 and AFM-3, differing from AFM-1 by one amino acid substitution each, shared 86.2% and 86.6% amino acid sequence identity with NDM-1, respectively. Phylogenetic analysis confirmed the close relationship between AFM and NDM. Expression of AFM and NDM-1 under their native promoters in DH5α and PAO1 led to elevated MICs for all tested β-lactams except aztreonam. Comparable catalytic abilities were observed for AFM and NDM-1 when hydrolysing nitrocefin, cefepime, imipenem and biapenem, whereas for other tested β-lactams AFM displayed weaker enzymatic activities. Modelling AFM structure revealed a characteristic αβ/βα fold with two zinc-binding active sites. Conclusions: AFM from clinical P. aeruginosa isolates demonstrated β-lactamase activity comparable to NDM-1. Co-carriage of bla AFM and bla KPC renders clinical P. aeruginosa isolates non-susceptible to all antipseudomonal β-lactams. The association of bla AFM genes with translocatable genetic elements and plasmids highlights their concerning potential for dissemination.